Training in Harmonizing Langgam and Modern Music as Accompaniment for Makassar Regional Songs - Karta Jayadi; Andi Taslim Saputra; Mas’ud Uqbah Al Ansyari; Khaeruddin Khaeruddin; Andi Agussalim Aj (Universitas Negeri Makassar, 2026)
This Community Service Program (PKM) focuses on strengthening local identity thru training, performances, and the digitalization of Makassar regional songs using an approach that harmonizes traditional and modern music. This activity is a response to the lack of appreciation from the community for Makassar regional songs, the low number of traditional music performances, and the absence of effective dissemination strategies in the digital era. The implementation of the activity began with socialization to local artists, traditional musicians, art communities, and the general public. This stage introduces the basic concepts of Langgam Makassar, its musical history, and its potential as a bridge between tradition and modernity. The socialization continued with the exploration of the repertoire of Makassar regional songs and the analysis of old recordings to understand the vocal character, rhythm, and melody that are the main identities of this regional music. The core stage of the activity involved musical training. After the training, the activities continued with performances held in several areas such as Barru, Sidrap, Makassar, Malino, and other cities. This performance serves as a space for appreciation as well as a performative test of the training outcomes. This program has a significant impact on the development of local musicians' capacities, the revitalization of regional songs, and the enhancement of cultural appreciation. In addition, this activity demonstrates that the collaboration between tradition and modernity, along with the utilization of digital technology, can create models of art production and learning that are relevant to the contemporary context. In the future, this program is designed to continue thru the development of new repertoires, the formation of community study groups, the expansion of performances, and the establishment of a digital portal as a center for the documentation of Makassar Langgam music.